1998
DOI: 10.1086/302111
|View full text |Cite
|
Sign up to set email alerts
|

A Second Locus for Familial High Myopia Maps to Chromosome 12q

Abstract: Myopia, or nearsightedness, is the most common eye disorder worldwide. "Pathologic" high myopia, or myopia of <=-6.00 diopters, predisposes individuals to retinal detachment, macular degeneration, cataract, or glaucoma. A locus for autosomal dominant pathologic high myopia has been mapped to 18p11.31. We now report significant linkage of high myopia to a second locus at the 12q21-23 region in a large German/Italian family. The family had no clinical evidence of connective-tissue abnormalities or glaucoma. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
124
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(125 citation statements)
references
References 18 publications
1
124
0
Order By: Relevance
“…The Epyc gene is located in the mapping interval of MYP3, which has been suggested to be a candidate gene for high myopia [28,29]. The EPYC protein is predominantly expressed in cartilage, and it is important for fibrillogenesis through the regulation of collagen fibrils [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The Epyc gene is located in the mapping interval of MYP3, which has been suggested to be a candidate gene for high myopia [28,29]. The EPYC protein is predominantly expressed in cartilage, and it is important for fibrillogenesis through the regulation of collagen fibrils [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Hereditary [17][18][19][20][21][22] and environmental [23][24][25] factors have been postulated to be responsible for myopia and myopic progression. Our study found that the incidence of children who revealed myopic progression or stability, or even regression may be related to whether or not their parent(s) suffered from myopia.…”
Section: Discussionmentioning
confidence: 99%
“…An Ïł4.6-kb NotI/ MluI zebrafish genomic DNA fragment containing the 5Ј portion of the zebrafish lumican gene was amplified by PCR and subcloned into the pBluescript SK vector (Stratagene, La Jolla, CA). The insert was sequenced, using T 3 , T 7 , and walk-in primers, by the DNA core of the Department of Molecular Genetics, National Taiwan University.…”
Section: Methodsmentioning
confidence: 99%
“…biglycan (Xq27ter), decorin (12q21-22), lumican (12q21. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], and DSPG3 (12q21) (4 -9). Our previous study showed that certain variations (rs3759223 (C3 T)) of single nucleotide polymorphism in the lumican regulatory region may influence the promoter activities of lumican and affect fibrillogenesis in myopic eyes (10).…”
mentioning
confidence: 99%